ROLE OF TRANSLATION IN THE GLOBALIZATION OF LITERATURE (Modern education and development, 2024)
This article discusses the role of translation is essensial for literature. Translation plays an essential role in enabling communication and fostering mutual understanding in a globalized world. It connects diverse cultures, supports international trade, advances education, and bridges the gaps between nations by preserving the meaning and context of ideas across languages. It serves learners to understand translating informations in any foreign language. There some reserchers and their reserch for students to improve their knowledge and enhance horizon.